Organogels from functionalized T-shaped pi-conjugated bisphenazines - Jang, Kyoungmi (Langmuir : the ACS journal of surfaces and colloids, 2010)
This paper reports the electronic and organogelation properties of novel T-shaped bisphenazines functionalized with alkyl side groups and small peripheral cyano (CN) or aldehyde (CHO) substituents. UV-vis spectroscopy and cyclic voltammetry show the effect of the position, type, and number of the peripheral substituents on the electronic properties of the entire system. Interesting organogelation properties including a thixotropic behavior were observed from these T-shaped bisphenazines. We describe important findings from an in-depth characterization on the fibers formed by organogelation: (i) The position of the peripheral substituents influences the fiber morphology by modulating the intermolecular CN (or CHO) interaction and the pi-pi stacking. (ii) Compounds with CHO groups form islands of fiber aggregates, which is not the case for compounds with CN groups. (iii) Decyl-substituted compounds show higher gelation temperatures (i.e., produce stronger gels) than hexadecyl-substituted ones. (iv) The thixotropic behavior originates from an extensive three-dimensional entanglement of very thin, flexible fibers